The political Situation in The southern Arabian peninsula in The sixth century. - Kharbotli , Shukran; Mohamma, Yunis (Tishreen University Journal- Arts and Humanities Sciences Series, 2017)
This article Talks about the important of the Arabian peninsula site and it's surrounding sbates . The article also monitors Political unrest in the southern Arabian Peninsula in the sixth century and surrounding states (Byzantium-Ethiopious-Persians)in-Fuelling-wars. . Where The intervention and Which Occupation Ethiopians and Byzantium 524a.d and drop Alhamirih state and impose a political system and anew administrative and military Wouldn't accept the Arabian peninsula residents who blast Gallop where persian intervention in 575a.d. to expel Ethiopians From Southern Arabian peninsula and impose a new Political system where the situation continues This way until the Islamic conquest of this region.